(untitled) (Journal of the College of Education for Women, 2019)
Linguistic taboos exist in most cultures. Tabooed words are generally being culturespecificand relating to bodily functions or aspects of a culture that are sacred. Such words areavoided, considered inappropriate and loaded with affective meaning and failing to adhere to.Strict rules, often, governing their use and lead to punishment or public shame. These taboowords can be used as a way of violating social deixis represented by four types of honorifics;addressee, referent, bystander, and finally setting honorifics. This paper shows how thesetaboo words are used in Kenneth Bernard’s play La Justice or The Cock that Crew from thetheatre of the Ridiculous as means of violating social deixis in its four types. The result showsa higher frequency of violating addressee honorifics as the actors use too many taboo wordsin interacting with each other. Bernard, the play writer, aims at showing the truth about theworld we live in, a world of arbitrary ruthless powers, of butchers and helpless victims.Key words: taboo, social deixis, honorifics, Kenneth Bernard, theatre of ridiculous